2020
DOI: 10.1038/s41598-020-68083-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult pancreatoblastoma: clinical features and Imaging findings

Abstract: The objective of this study was to illustrate the clinical, CT, MRI, and 18 F-FDG PET/CT features of adult pancreatoblastoma, an extremely rare disease. In this study, the clinical and imaging features of seven adult patients with pathologically confirmed pancreatoblastoma were retrospectively analyzed. The following parameters were evaluated: size, location, shape, margination, solid-cystic ratio, CT attenuation values or signal intensity and contrast enhancement pattern. We also analyzed whether abnormal FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…Pancreatic duct dilatation was found in our study, with tumour tissue in the pancreatic duct observed on microscopic examination, which indicates that pancreatic duct dilation caused by adult PB is common. Mild enhancement was observed in enhanced scans in a previous report [ 9 ]. Mild enhancement in the AP was observed in two tumours in our study, showing a slow-in and slow-out pattern, similar to previous reports.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Pancreatic duct dilatation was found in our study, with tumour tissue in the pancreatic duct observed on microscopic examination, which indicates that pancreatic duct dilation caused by adult PB is common. Mild enhancement was observed in enhanced scans in a previous report [ 9 ]. Mild enhancement in the AP was observed in two tumours in our study, showing a slow-in and slow-out pattern, similar to previous reports.…”
Section: Discussionmentioning
confidence: 50%
“…The strengthened enhancement is related to the pathology finding of a vascular structure around the squamoid corpuscles, which is a new finding that will be helpful for diagnosing adult PB. In the MRI sequence, isointensity was found on T1WI, while hyperintensity was found on T2WI in two cases, with limited diffusion [ 9 ]. Contrast-enhanced scans were consistent with CT scans, with significant enhancement in the AP [ 1 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical information, including age, sex, clinical symptoms, tumor location, and tumor size, was collected from electronic medical records and pathological results (10.6084/m9.figshare.20073167). Multimodality imaging, including contrast-enhanced CT, MRI, EUS, and nuclear medicine imaging, was performed as previously described, and data were recollected through electronic medical systems (7,(9)(10)(11). Two experienced radiologists independently evaluated the variables of CT/MRI on a PACS workstation (GE Centricity PACS V 3.0, GE Healthcare, Milwaukee, WI, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The aetiology is unknown. Although most tumours are sporadic[ 11 - 15 ], few adult pancreatoblastomas have been described in the setting of familial adenomatous polyposis (FAP)[ 8 , 9 ]. Rare cases in children have been associated with Beckwith-Wiedemann syndrome[ 16 , 17 ].…”
Section: Aetiologymentioning
confidence: 99%
“…Most patients are symptomatic, with very few cases discovered incidentally during routine examination and imaging[ 4 , 10 , 11 ]. There are no symptoms unique to pancreatoblastomas.…”
Section: Clinical Presentationmentioning
confidence: 99%